Round-robin test of medium-energy ion scattering for quantitative depth profiling of ultrathin HfO2/SiO2/Si films - Min, Won Ja; Marmitt, Gabriel; Lyudmila Goncharova; Kenji Kimura; Torgny Gustafsson; Matt Copel; Jungkyu Ko; HyungIk Lee; Sungho Lee; 채근화; Jaap van den Berg; Kagnwon Jung; et al. (WILEY, 2019)
Medium-energy ion scattering (MEIS) has been used for quantitative depth profiling with single atomic layer resolution to determine the composition, thickness, and interface structure of ultrathin films and nanoparticles. To assure the consistency of the MEIS analysis, an international round-robin test (RRT) with nominally 1-, 3-, 5-, and 7-nm thick HfO2 films was conducted among 12 institutions. The measurements were performed at each participating laboratory under their own conditions, and the collected data were analyzed. For the data analysis, the Moliere potential, the stopping and range of ions in matter (SRIM) 95 and new fitted electronic stopping power and the Chu straggling were used. For analyzing the MEIS data from the magnetic sector and electrostatic analyzers, the neutralization corrections of Marion and Young for 100-keV H+ and He+ ions and of Armstrong for 400- to 500-keV He+ ions were used. The standard deviations were 5.3% for the composition, 15.3% for the thickness, and 13.3% for the Hf content, and they were improved to 7.3%, 4.5%, and 7.0% by using refitted electronic stopping powers based on the experimental data. Hence, this study suggests that correct electronic stopping powers are critical for quantitative MEIS analysis.